2011
DOI: 10.1534/genetics.111.130815
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Rapidly Evolving Male Genital Morphology inDrosophila

Abstract: The external genitalia are some of the most rapidly evolving morphological structures in insects. The posterior lobe of the male genital arch shows striking differences in both size and shape among closely related species of the Drosophila melanogaster species subgroup. Here, we dissect the genetic basis of posterior lobe morphology between D. mauritiana and D. sechellia, two island endemic species that last shared a common ancestor 300,000 years ago. We test a large collection of genome-wide homozygous D. mau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(96 citation statements)
references
References 119 publications
(134 reference statements)
5
91
0
Order By: Relevance
“…Epandrial posterior lobes provide the strongest discriminatory characters between species of the melanogaster complex (Fig. 1B–C, E–F, H–I, K–L) and have been subject to extensive investigations aiming at identifying the genetic basis of morphological divergence [45][50]. We found that average female pouch area correlates with average male lobe area in the melanogaster complex species (Spearman’s rank correlation: r  = 1.00, P <0.157; Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Epandrial posterior lobes provide the strongest discriminatory characters between species of the melanogaster complex (Fig. 1B–C, E–F, H–I, K–L) and have been subject to extensive investigations aiming at identifying the genetic basis of morphological divergence [45][50]. We found that average female pouch area correlates with average male lobe area in the melanogaster complex species (Spearman’s rank correlation: r  = 1.00, P <0.157; Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Unfortunately the molecular mechanisms of shape divergences is poorly studied. A limited knowledge is slowly accumulating on genomic processes of the subtle shape divergences, pertaining exclusively to some reference elite organisms like Drosophila, but highly deteriorated by virtuality (Franco et al 2006, Masly et al 2011, Mc Neil et al 2011, Schafer et al 2011.…”
Section: Cooperation Asymmetrymentioning
confidence: 99%
“…Besides directly inducing maintenance and proliferation of germ line stem cells in relation to nutrient availability, the ISP also affected spermatocyte growth in testes of male D. melanogaster (Ueishi et al, 2009; McLeod et al, 2010; Wang et al, 2011). A study in other Drosophila species suggested that the ISP also influences the growth of male external genitalia (Masly et al, 2011). Studies on different species of horned beetles suggested that the ISP also mediates the growth of the horns that are used by males of these species for competing with rival males, when protecting female mating partners (Emlen et al, 2012; Lavine et al, 2013).…”
Section: The Isp and Male Reproductive Physiologymentioning
confidence: 99%